Factors that affecting student’s academic performance among final year students in UiTM Kampus Bandaraya Melaka / Nur Syuhada Atirah Mohd Azhan - Mohd Azhan, Nur Syuhada Atirah (Faculty of Business and Management, 2019)
The principal objective of this study is to identify the factors influencing the student’s academic performance on final year student in UiTM Kampus Bandaraya Melaka. This helps to rise a better understanding on the factors that affecting student’s performance and also to contribute to the UiTM Kampus Bandaraya Melaka. The factors subject to identify includes student’s communication skills, study habits, learning facilities and student’s attendance and the dependent variable is student’s academic performance. The hypotheses are designed to explain the relationship between the independent variables and dependent variable. Since the sampling method that has been used in this research is convenient. The data collected through the questionnaires are tested using the Statistical Package for Social Sciences (SPSS) software to run the test for the analysis and interpretation purpose. While, the relationship between the variables was tested using multiple regression analysis. Finding shows that there is a significance relationship between independent variables; student’s communication skills, study habits, learning facilities and student’s attendance and dependent variable; student’s academic performance. Several limitations were encountered in this study as well. Such include the researcher has lack of time to conduct this study, researcher also lack of information and resources to accomplish this research and lastly, the researcher lack of response from respondent, since the respondent provides less commitment to give their feedback. But, all these limitations can be overcome through careful procedures and other methods.